Some notes on lexical differences between male and female in the Spanish language of Lima - Lesevic, Cecilia (1989)
Differences between women and men language are a result of their contrasting social role, adjudicated and learned during the socialization process. Thus men and women belong to heterogeneous sociolinguistics sub-cultures, with differing interests, reactions and behaviors regarding language. In Lima 's speech this is mainly shown through the election of lexical varieties for verbal agression, for speaking about the other sex, the partner and sexual matters (more euphemistic in the feminine variety and straighter in the male one); and also through certain linguistic taboos reflecting the social organization, with dominant men and dominated women.